A STUDY ON THE EFFICIENCY OF PHYLLANTHUS NIRURI IN AMELIORATING THE DRUG INDUCED OXIDATIVE STRESS IN Oreochromis mossambicus AND ITS COMPARISON WITH A HERBAL FORMULA LIV 52 - REMA, L. P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Hepatoprotective and antioxidant potential of Phyllanthus niruri and Liv.52, in relieving the paracetamol induced hepatotoxicity in Oreochromis mossambicus is compared. Exposure of fish to different concentrations of Paracetamol showed increase in TBA value and a decrease in the total protein content. Phyllanthus niruri and Liv.52 supplied through feed probably decreases the reactive oxygen species (ROS) resulting in lower TBA value indicating reduction in lipid peroxidation. Lower protein level in these groups may be due to enhanced utilization of proteins for active metabolism and growth. Fish fed with Phyllanthus niruri showed lower TBA value than the paracetamol exposed animals, but the fish fed with commercially produced Liv.52 showed even lower TBA value than those fed with Phyllanthus niruri, indicating the greater protective effect of commercially available drug Liv.52 which is a combination of many medicinal plants. The data are statistically analysed using t test.